Vaccinating against Helicobacter pylori in the developing world - Zawahir, Shamila (Landes Bioscience, 2013)
Helicobacter pylori infects more than half the world’s population and in developing nations the incidence can be over 90%. The morbidity and mortality associated with H. pylori-associated diseases including ulcers and gastric cancer therefore, disproportionately impact the developing world. Mice have been used extensively to demonstrate the feasibility of developing a vaccine for H. pylori infection, and for testing antigens, routes of immunization, dose, and adjuvants. These successes however, have not translated well in clinical trials. Although there are examples where immune responses have been activated, there are few instances of achieving a reduced bacterial load. In vivo and in vitro analyses in both mice and humans demonstrates that the host responds to H. pylori infection through the activation of immunoregulatory mechanisms designed to suppress the anti-H. pylori response. Improved vaccine efficacy therefore, will require the inclusion of factors that over-ride or re-program these immunoregulatory rersponse mechanisms.